6‐Substituted 2‐Aminopurine‐2′‐deoxyribonucleoside 5′‐Triphosphates that Trace Cytosine Methylation - von Watzdorf, Janina (Chembiochem, 2016)
Gene expression is extensively regulated by the occurrence and distribution of the epigenetic marker 2′‐deoxy 5‐methylcytosine (5mC) in genomic DNA. Because of its effects on tumorigenesis there is an important link to human health. In addition, detection of 5mC can serve as an outstanding biomarker for diagnostics as well as for disease therapy. Our previous studies have already shown that, by processing O (6)‐alkylated 2′‐deoxyguanosine triphosphate (dGTP) analogues, DNA polymerases are able to sense the presence of a single 5mC unit in a template. Here we present the synthesis and evaluation of an extended toolbox of 6‐substituted 2‐aminopurine‐2′‐deoxyribonucleoside 5′‐triphosphates modified at position 6 with various functionalities. We found that sensing of 5‐methylation by this class of nucleotides is more general, not being restricted to O (6)‐alkyl modification of dGTP but also applying to other functionalities.